Patrick Geddes: sociologist, environmentalist and town planner - Munshi, Indra (2000)
Patrick Geddes' pioneering work in applying sociological understanding of environmental concerns to town planning did not get due recognition during his own lifetime and also subsequently. But, with the quest for seeking inter-linkages between various specialised streams of knowledge gaining momentum of late, Geddes' interdisciplinary inquiries into natural and social sciences have gained significance within contemporary academia. - Reproduced
Keywords: Urban planning; Environmentalists; Sociologists; Geddes, Patrick